2023
DOI: 10.1002/vms3.1097
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude and practice (KAP) of smallholder farmers on foot‐and‐mouth disease in Cattle in West Kazakhstan

Abstract: Background: This study was performed to assess the knowledge, attitudes and practices (KAPs) of farmers and veterinary professionals towards foot-and-mouth disease (FMD) in the area studied. Methods:The study was based on a comprehensive questionnaire administered through face-to-face interviews. Between January and May 2022, 543 households and 27 animal health practitioners (AHP) were visited in 4 provinces of the West Kazakhstan region to assess their KAPs towards FMD.Results: A large proportion of herd owne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…Since most poultry are located within relatively small areas. But, despite this possibility, the number of poultry farms and their livestock in Kazakhstan is only increasing every year (Bayantassova et al, 2023). The economic prerequisites that contribute to this are the annual increase in the imported purchase of poultry meat and eggs to meet the demand of the population of Kazakhstan.…”
Section: Discussionmentioning
confidence: 99%
“…Since most poultry are located within relatively small areas. But, despite this possibility, the number of poultry farms and their livestock in Kazakhstan is only increasing every year (Bayantassova et al, 2023). The economic prerequisites that contribute to this are the annual increase in the imported purchase of poultry meat and eggs to meet the demand of the population of Kazakhstan.…”
Section: Discussionmentioning
confidence: 99%
“…Research has been carried out on farmers' understanding of FMD in various nations, such as [7] in Afghanistan, [8] in Kenya, [9] in India, [10] in Nigeria, [11] in West Kazakhstan (and [12] in Ethiopia. Nonetheless, there has been no investigation conducted on farmers' awareness of FMD in Sulawesi.…”
Section: Introductionmentioning
confidence: 99%
“…Amanova et al (2020), leads to significant economic losses, which are associated with the death or forced slaughter of infected animals, a decrease in their productivity, losses on veterinary, sanitary, and quarantine measures. Therefore, the most common method of preventing this viral disease is active immunisation of all susceptible livestock (Bayantassova et al, 2023). The materials provided by M. Legnardi et al (2022) indicated that USD 10.1 million was spent on animal vaccination in Kyrgyzstan only for preventive work in the period from 2017 to 2020.…”
Section: Introductionmentioning
confidence: 99%